Analisis Implementasi Good Governance Terhadap Pengelolaan Keuangan Organisasi Nirlaba Pada Yayasan Pendidikan Rezki Prasetya Makassar - Meinarti, Suci; Sahade; S, Masnawaty (Yayasan Sagita Akademia Maju, 2024)
This research aims to determine and analyze the implementation of good governance principles in financial management implemented at the Rezki Prasetya Makassar Education Foundation. The population of this research is the financial report of the Rezki Prasetya Education Foundation Makassar, while the sample is the financial report of the Rezki Prasetya Education Foundation for 2023. The data collection techniques used are interviews and documentation. The data analysis technique used in this research is descriptive qualitative. This technique begins with conducting interviews, collecting data or documents from samples, processing the data, and drawing conclusions. From the research results, it shows that the implementation of good governance towards financial management at the Rezki Prasetya Education Foundation Makassar has not fully met the indicators applied to measure the principles of Good Governance such as regulations governing forms of transparency at the Rezki Prasetya Education Foundation are not yet available, the Rezki Prasetya Education Foundation Makassar in making financial reports, they have not followed ISAK 35 which regulates the financial reports of non-profit organizations.